PENGARUH QUOTES ISLAMI TERHADAP POLA PIKIR SESEORANG - Fani Rachma; Suci Oktaviani Novita; Latifah Cahya Dewi; Pandu Hyangsewu (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
A positive mindset is one way to reduce the prevalence of mental illness. So that we always think positively, there are already many Islamic quotes on various social media. These Islamic quotes contain advice, verses from the Qur'an, hadith, etc. In this study, we can see how the influence of Islamic quotes on a person's mindset. The method used The method used in this study is a survey research method. This method is a research method carried out by utilizing surveys or data collection through research respondents. Based on the results obtained by researchers from the distribution of questionnaires, the effect of Islamic quotes on positive thinking patterns is very high. After this research, it is hoped that many people will know more about how Islamic quotes influence a positive mindset.